2004
DOI: 10.1111/j.1559-1816.2004.tb02563.x
|View full text |Cite
|
Sign up to set email alerts
|

How the Defendant's Emotion Level Affects Mock Jurors' Decisions When Presentation Mode and Evidence Strength Are Varied1

Abstract: Two experiments (N = 443) were conducted to investigate the effects of a defendant's emotion level during testimony on mock jurors' decisions. In Experiment 1, the defendant's level of emotion (low, moderate, high) and mode of presentation (audio, video) were varied. The defendant displaying a low level, as opposed to a higher level of emotion was perccived as more guilty and less credible. In Experiment 2, using only the video mode, emotion level and evidence strength (strong, weak) were varied. Defendant ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Similarly, R-processors may be more likely to perceive the evidence in a case differently (i.e., less ambiguous), also influencing their judgments. For example, strong displays of defendant emotionality have led to less guilty verdicts and punitiveness when evidence against the defendant is weak (Heath et al, 2004). However in our study, the case was intentionally ambiguous, leaving room for individual juror interpretations of evidentiary strength.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Similarly, R-processors may be more likely to perceive the evidence in a case differently (i.e., less ambiguous), also influencing their judgments. For example, strong displays of defendant emotionality have led to less guilty verdicts and punitiveness when evidence against the defendant is weak (Heath et al, 2004). However in our study, the case was intentionally ambiguous, leaving room for individual juror interpretations of evidentiary strength.…”
Section: Discussionmentioning
confidence: 47%
“…Finally, it may be the timing of emotional information displayed (especially by defendants) that influences sentencing outcomes more so than simply the presence of emotionality. For example, Heath et al (2004) reported that greater emotional displays prior to guilt determinations led to less punitive sentencing. However, extant research suggests that a defendant's emotional display after a guilty verdict may be of greater diagnostic value in sentencing outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also have imagined situations even more gruesome than the actual photographs that were shown in the photograph-present condition. In a study by Heath, Grannemann, and Peacock (2004), mock jurors who were provided information by audio perceived the defendant's emotion to be stronger than did mock jurors who watched a video. The researchers suggested that information provided by audio does not limit the receivers' visualization.…”
Section: Gruesome Photographsmentioning
confidence: 90%
“…Research findings have shown that offenders who exhibit stronger emotion are favoured with fewer convictions and more lenient sentences, whereas offenders whose level of emotional display is low are perceived as more culpable and less credible 84 . The influence of emotional displays on sentencing was most pronounced when the strength of the evidence against the defendant was weak.…”
Section: Emotional Displays By Offendersmentioning
confidence: 95%